2013
DOI: 10.1177/1076029613485283
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness in Patients With Slow Coronary Flow and Its Association With Neutrophil-to-Lymphocyte Ratio

Abstract: The NL ratio is significantly associated with reduced coronary blood flow, and elevated N/L ratio might be an independent predictor for the presence of SCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 37 publications
2
37
2
Order By: Relevance
“…Measuring the neutrophil-to-lymphocyte ratio (NLR) is an inexpensive and convenient way to identify systemic inflammation in the body [6]. This simple test can be used for critically ill patients with systemic inflammation to evaluate the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the neutrophil-to-lymphocyte ratio (NLR) is an inexpensive and convenient way to identify systemic inflammation in the body [6]. This simple test can be used for critically ill patients with systemic inflammation to evaluate the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, not only RDW but also mean platelet volume, 10 neutrophil lymphocyte ratio, 11 CRP, and uric acid are easy methods to evaluate the cardiovascular disease of patients. 12 These markers might be useful in clinical practice.…”
Section: To the Editormentioning
confidence: 99%
“…Recent studies have demonstrated that pregnant women with HG have higher inflammatory markers when compared to healthy pregnant women without HG in the first trimester. Measuring white blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and red blood cell distribution width (RDW) is an inexpensive and convenient way to identify systemic inflammation in the body (12)(13)(14)(15). Studies have shown that NLR, PLR, and RDW values are highly associated with the prognosis of diseases related to inflammation (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%